The Martian [compact disc, unabridged] : a novel - Weir, Andy (Brilliance Audio, 2014)
Mark Watney was nearly killed by a dust storm on Mars and was abandoned by his crew who thought him dead. Now he's all alone with no way of letting Earth know he's alive, which doesn't matter because his supplies would run out before they'd get there. Either way, the environment or human error will likely kill him first. Not giving in, Mark works to survive, battling obstacle after obstacle, but will it be enough?